Applications of Conventional Vibrational Spectroscopic Methods for Batteries Beyond Li‐Ion. Issue 8 (26th March 2018) - Deng, Yuanfu; Dong, Shengyang; Li, Zhifei; Jiang, Heng; Zhang, Xiaogang; Ji, Xiulei
Abstract: Advanced energy‐storage devices are in tremendous demand to meet the ever‐growing electrification of the economy. To design batteries, it is critical to understand the evolving structures of the electrode materials, the compositions of the solid electrolyte interphase, and the reaction intermediates during the electrochemical processes. To this end, a plethora of characterization techniques are employed in battery research to bridge the fundamental understanding to practical optimization of battery systems. Vibrational spectroscopy methods, including Raman spectroscopy, and Fourier transform infrared (FTIR) spectroscopy are powerful analytic tools for the purposes of battery studies. Here, the usage of Raman and FTIR spectroscopy techniques for secondary batteries, such as lithium‐ion batteries, lithium–sulfur batteries, lithium–oxygen batteries, sodium‐ion batteries, and potassium‐ion batteries, is described. Abstract : The recent progress on employing Raman and infrared spectroscopy techniques for emerging secondary batteries, such as lithium–sulfur batteries, lithium–oxygen batteries, sodium‐ion batteries, and potassium‐ion batteries, is described. An introduction for new researchers in the field of energy storage is provided, and these fantastic tools for the study of such batteries are highlighted.